O valor político dos testemunhos: os surdos e a luta por reconhecimento na internet - Regiane Lucas de Oliveira Garcez (2008)
This work researches how the deaf, who communicate through Sign Language, use their testimonies to take up a struggle for recognition of their identities and then to reveal new values about deafness. This research is guided by the Theory of Recognition, proposed by Axel Honneth and Charles Taylor. In this approach, we consider the intersubjetive character, which leads the construction of identities and the struggle for recognition, the division of this struggle in three dimensions private, legal and social relationship, and the increased struggle which conducts to a moral evolution of society. In this increased struggle, the deaf use their testimonies to response to some deeplyrooted values, such as disability (due to deafness) or the low value of Sign Language. We research how the deafs responses are produced in two different virtual environments. The first is the website of National Federation of Education and Integration of the Deaf (Feneis) and the second is the social networking service, available in the Internet, called Orkut. In thesecond virtual space, we take our empiric material from the discussion foruns. Since these two virtual environments are quite distinct from each other, we have analyzed them of two different forms. In the Federations website, the struggle for recognition has been analyzed regarding the presumed other, who represents the actual values about thedeaf. In the Orkut, this other is noticed in the discussions. We have worked on theories of everyday chat and political conversation to show that the ways of using the testimonies are different in discussion contexts and static contexts, such as in the website of Feneis.